Improvement of Student’s Social Relationships Through Content Mastery Services - Nurul Allivia; Christine Masada Hirashita Tobing; Nani Al Muin (Asosiasi Asesmen Pendidikan (AAP), 2025)
This research aims to examine the effectiveness of content mastery services in improving student social relationship at SMK Dinamika Pembangunan 2 East Jakarta. The research method used in this research is quantitative, utilizing a survey and a pre-test and post-test quasi experimental design. The population in this research was 996 people, with a sample of 68 people, 32 students in the experimental class, 31 students in the control class, 3 guidance and counseling teachers, and 2 class teachers. A quasi experimental research design was used with the aim of investigating cause and effect relationship. This research used data collection instruments, namely questionnaires, interviews, behavioral observations, and documents. In the questionnaire, respondents (students) filled out statement on paper. At the beginning, respondents filled out the pre-test questionnaire, then the researchers conducted the treatment, and finally, respondents were asked to fill out the final post-test used to obtain data or information about student’s social relationship. This research used information services and content mastery services as its treatment media. Pre-test and post-test data were analyzed using the Paired Sample t-Test. The results of the analysis showed that there was a significant difference between the pre-test and post-test scores (p < 0.05). In the experimental class, there was an increase in student’s social relationship after being given content mastery services, while in the control class, there was a decrease. This research provides an empirical basis for the development of structured content mastery services that are useful for supporting student’s social relationships in the community.